LU Filoloģijas un filozofijas fakultātes klasiskās filoloģijas studenta Jāņa Gefkina (1911-1938) izvadīšana Rīgas Meža kapos - Zembahs, Frcis (?) (Friča (?) Zembaha Foto un palielinājumu darbnīca, 1938)
Rīgas Valsts 1. ģimnāzijas absolventa, LU Filoloģijas un filozofijas fakultātes Filoloģijas nodaļas klasiskās filoloģijas studenta un latviešu studentu korporācijas Fraternitas Lettica biedra Jāņa Gefkina (1911-1938) bēres 1938. gada maijā Rīgas Meža kapos. 1. FOTOGRĀFIJA - Latviešu studentu korporācijas Fraternitas Lettica goda sardze ar sērām ierodās uz sava aizgājušā biedra Jāņa Gefkina bērēm. 2. FOTOGRĀFIJA - zārka izvešana no kapličas uz apbedīšanas vietu Rīgas Meža kapos. 3. FOTOGRĀFIJA - bēru gājiens

The coffin of Jānis Gefkins (1911-1938), a graduate of Riga State Gymnasium No.1, student of classical philology at the Faculty of Philology and Philosophy of the University of Latvia and member of the Latvian student fraternity Fraternitas Lettica. PHOTO 1 - being taken from the chapel to his burial place in Riga Forest Cemetery in May 1938. PHOTO 2 - The Honour Guard of the Latvian student fraternity Fraternitas Lettica mournfully attends the funeral of their deceased member. PHOTO 3 - The honour guard of the Latvian student fraternity Fraternitas Lettica mournfully accompanies its deceased member to his burial place in the Riga Forest Cemetery.
The coffin of Jānis Gefkins (1911-1938), a graduate of Riga State Gymnasium No.1, student of classical philology at the Faculty of Philology and Philosophy of the University of Latvia and member of the Latvian student fraternity Fraternitas Lettica. PHOTO 2 - being taken from the chapel to his burial place in Riga Forest Cemetery in May 1938. PHOTO 2 - The Honour Guard of the Latvian student fraternity Fraternitas Lettica mournfully attends the funeral of their deceased member. PHOTO 3 - The honour guard of the Latvian student fraternity Fraternitas Lettica mournfully accompanies its deceased member to his burial place in the Riga Forest Cemetery.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Classical philology; Latviešu studentu korporācija "Fraternitas Lettica"; Klasiskā filoloģija; Studentu akadēmiskās mūža organizācijas; Studentu korporācija; Bēres; The University of Latvia; Classical Philology; Student academical lifetime organisations; Student fraternities; Funeral; Korporācijas biedri